The Company You Keep: How an Organization’s Horizontal Partnerships Affect Employee Organizational Identification - Cornwell, T. Bettina; Howard-Grenville, Jennifer; Hampel, Christian E. (Academy of Management Review, 2018)
Despite scholars’ recognition of the importance of external dynamics to employee organizational identification, this factor remains underexplored in today’s evermore interdependent organizations. We theorize about how organizational identification can be influenced by an employer’s horizontal partnerships with entities such as sports teams or charities. Drawing on insights from the organizational identification literature and marketing literature, we explore how events concerning an organization’s horizontal partner become salient to employees, how employees evaluate the implications of the partnership, and how their identification may shift as a result. Surprisingly, our model reveals that partnerships having low congruence may lead to significant positive identification shifts for some individuals, whereas partnerships that are seemingly positive for an organization may result in negative identification shifts. Our theorizing makes two important contributions. First, it introduces the potential of horizontal relationships with other organizations to shape the important work relationship of identification with the focal employing organization. Second, it outlines the processes through which horizontal partners can make a difference in work relationships and sets the stage to better understand how they can strengthen and hinder these relationships, as well as encroach on nonwork life.